Present status, problem and prospect of duck farming in rural areas of Mymensingh district, Bangladesh (Asian Journal of Medical and Biological Research, 2016)
The study was conducted to know the present status, existing production system of duck and assess the potentiality of duck rearing in rural areas of Mymensingh district in Bangladesh. Data were collected randomly from 50 duck rearing farmers using a pre-tested interview schedule during March to May 2010 from several villages under sadar upazilla of Mymensingh. The results reveal that most of the farmers (60%) were middle aged. About 32% farmers were illiterate. Most of the farmers (52%) reared deshi duck and duck population per household was 11.1. About 80% wife of farmers household were responsible for duck rearing. All farmers reared duck in semi scavenging system. About 36% farmers used wood and tin for construction of duck house and 94% farmers used bedding materials for their duck house. All farmers used rice in the diet for duck and 62% farmers accumulated rice and rice polish to make diet for their ducks. About 40% farmers provided on an average of 121.91g supplemental diet to each duck/day and cost of the diet was Tk. 0.85/duck/day. Most of the farmers (72%) provided diet to their ducks twice a day. The age and weight of duck at maturity were 183.6 days and 1.69 kg, respectively. Egg production/duck/year and weight of each egg were 117.5 nos and 63.8g, respectively. All farmers incubated duck egg under broody hen and they got 85.83% hatchability on set eggs. Most of the farmers (52%) mentioned that most prevalent disease of duck was cholera and their duck mortality was 15.2%. About 52% farmers controlled their duck disease with medication and only 14% farmers used vaccine to prevent duck disease. About 22% and 13.5% people did not consume duck meat and egg, respectively because of odour, asthama and allergy. Most of the farmers (50%) incubating duck eggs for ducklings. About 66% farmers purchased duckling by Tk. 24-25 and 58% farmers sell adult duck by Tk. 175-190. Most of the farmers (81.25%) stated that the duck farming is decreasing day by day. About farmers (51%) stated that reason of decreasing duck farming was lack of scavenging area. It was concluded that duck rearing knowledge of the farmers such as breeding, feeding, housing, prevention and control of diseases are not satisfactory of this areas. Introducing of improved duck breeds/varieties, training to duck farmers, ensuring vaccination to ducks, financial and technical support to the farmers could increase the duck rearing with increased household income and employment to youth, rural women and the small-holder marginal farmers.Asian J. Med. Biol. Res. June 2016, 2(2): 202-212